PENGARUH APLIKASI CAKE DALAM MENINGKATKAN KEMAMPUAN BAHASA INGGRIS MAHASISWA PGSD - Junaidi Junaidi; Alya Aulia Faiza (Yayasan Citra Dharma Cindekia, 2025)
In this era we can learn English through various media such as YouTube, games, applications, etc. However, in reality, there are many students who cannot speak English fluently. The aims of this study were (1) to find out the effectiveness of cake application in improving students' English skills, (2) to describe the obstacles students experience in learning English. Data collection techniques include interviews, observation, literature studies, reading tests. The results of the study were (1) students' English skills increased after learning through the